'Lost' taxa and their conservation implications. (16th May 2022) - Martin, T. E.; Bennett, G. C.; Fairbairn, A.; Mooers, A. O.
Abstract: While biological extinctions are predicted to rise sharply during the Anthropocene, extinction declarations are rare, partly due to inherent uncertainties in knowing when the last individual of a species has died. This has led to the growth of a group of 'lost' species that have not been observed in decades or even centuries, yet are not declared extinct, and as such possess an uncertain conservation status. The existence of such species may prove increasingly problematic as the extinction crisis worsens, given that their presence may create uncertainty with respect to conservation prioritization efforts and to our understanding of extinction rates. We provide the first assessment of the extent of lost taxa, defined as species that have not been reliably observed in >50 years yet are not declared extinct, for terrestrial vertebrates (amphibians, reptiles, birds and mammals). We reviewed information from IUCN Red List accounts within these Classes using a hybrid code‐based search/manual assessment approach, supplemented with consultation of recent literature. In total, we identify a total of 562 lost species (137 amphibians, 257 reptiles, 38 birds and 130 mammals). Of these, 13% (75 species) are listed as 'Possibly Extinct' by the IUCN. Lost species outnumber extinct species for all studied Classes except birds. They were mainly confined to the tropics (92.5%), with distributions being particularly concentrated in 'mega‐diverse' countries, as expected. Indonesia (69 species), Mexico (33 species) and Brazil (29 species) possessed the most lost species overall. Our results highlight the prevalence of lost taxa among terrestrial vertebrates and identify 'hotspots' for these species where future survey efforts should be prioritized. We suggest minor adjustments to IUCN Red List accounts to allow lost species to be better tracked, including more consistent use of the 'Possibly Extinct' marker and wider application of the 'last seen date' field. Abstract : Conceptual diagram showing the uncertain classification of lost species, which simultaneously overlap with both extant and extinct species. These lost species may become an increasingly important source of uncertainty in conservation prioritization efforts in the coming decades, particularly if their numbers grow as the effects of the Anthropocene intensify. Efforts to resolve their status represent an important priority for field scientists and conservation organizations.